Integrating digital learning and human capital: pathways to sustainable economic growth in Romania - Alexandra CONSTANTIN; Alexandra Ioana MURARIU; Radu-Alexandru BUDU (Theoretical and Applied Economics)

(untitled)
The digital transformation of education aims to equip the human capital with a set of digital skills characterized by complementarity that can be applied interdisciplinary. Besides, digitalization is often linked with economic development and efficiency, which led to the adoption of the Digital Education Action Plan 2021-2027 by the European Commission. As one of the EU-27 high-income member states, Romania fails in terms of digitalization of the human capital or economy. Hence, the main purpose of this study was to investigate the impact of digital education and human capital development on sustainable economic growth in Romania. The methodological approach used both qualitative and quantitative methods, like the regression model that allowed the quantification of relationships between variables. Data collection was applied for the period between 2020 and 2024. The main findings suggest that many systemic issues prevent Romania from taking advantage of its robust digital infrastructure. Despite the important growth potential presented by Romania, the lack of a clear innovation strategy to develop digitalization for sustainable economic growth had a very negative effect on the development of digital competencies of the human capital. Further research should focus on the role of digital skills in labour market resilience, the impact of digital education on regional economic disparities, and the governance and policy interventions in digital transformation.